Analysis of Peak Power Capacity on Rooftop Solar PV 1.25 kWp at Sun Conditions 90 Degrees - Satria, Habib; Syafii, Syafii; Aswardi, Aswardi (International Journal of Electrical, Energy and Power System Engineering, 2021)
This paper describes the optimization of energy conversion when solar radiation occurs at peak power conditions, namely at 11.00 am to 2.00 pm where the position of the sun is parallel to the layout of the PV Rooftop installation. The panels used are 5 units with the type of polycrystalline with a capacity of 1 panel unit consisting of 250 Wp. The position of the panels installed on the roof of the Andalas University building is based on an angle of 90o degrees with a position of ±255m above sea level. The advantages obtained when placed on the roof of the building are due to the minimal impact of shadow effects and environmental disturbances. Data retrieval using DC current and voltage sensors is then connected to the Arduino Uno microcontroller which is then interfaced in graphic form. Considerations in the installation of PV by reviewing the weather conditions at that time where the conditions were sunny and the air was clean with the aim that the performance when solar radiation entered the solar cells could be produced more optimally. Based on the data obtained at peak power, PV can convert DC power to 972.56 Wp. In the final stage of collecting data recorded on this PC, it can later be used as a reference for installing solar panels for household electricity scales in the West Sumatra region.